Crystal structure of catena-poly[diaqua-bis(μ2-1,3-di(1H-imidazol-1-yl)propane-κ2N:N′)cobalt(II)] tetrafluoroterephthalate, C26H28N8O6F4Co - Huang Xiao-Zhou; Lu Jiu-Fu (Zeitschrift für Kristallographie - New Crystal Structures)
C26H28N8O6F4Co, monoclinic, C2/m (no. 12), a = 15.7590(18) Å, b = 11.6981(15) Å, c = 9.1210(12) Å, β = 121.227(7)°, V = 1437.8(3) Å3, Z = 2, Rgt(F) = 0.0323, wRref(F2) = 0.0904, T = 293(2) K.